Efecto de tres fungicidas en el control de Perenospora farinosa en Chenopodium quinoa WILLD.Var. ILLPA-INIA en el Caserío Pueblo Nuevo-Santiago de Chuco - Gomez Benites, Elbar Bernabe (2016)
This research work entitled "Effect of three fungicides in controlling Perenospora farinosa a in Chenopodium quinoa Willd var. Illpa-Inia in the village of Pueblo Nuevo-Santiago de Chuco "was held from November 3, 2015 until 26 May 2016. It aimed to evaluate the effect of three fungicides in controlling Perenospora Farinosa in Chenopodium quinoa Willd for which the complete block design at random (DBCA) was used with three treatments (T1: application Bordales broth; T2: application of lime sulfur broth and T3: application sìlicosulfocàlcico broth) and a control (T0), with three repetitions; the population consisted of quinoa genetic material from the INIA-Huancayo. It was evaluated in the lower third of 10 plants incidence Peronospora farinosa expressed in percentage (%) and also evaluated in three individual sheets (one in the third) the severity of downy mildew by the percentage (%) of leaf area affected. The statistical evaluation was based on analysis of variance (ANOVA) and Tukey test the 0.05 level of significance. The results showed that the three fungicides had a significant effect in controlling Peronospora farinosa percentages expressing the incidence and degree of lower severity than the control. The fungicide that had the greatest effect in that control was the silicosulfocàlcico broth where the lowest percentage of incidence (35%) and less severity (2.13) on average was observed. In the yield per hectare it was also reflected this effect, as it was higher in treatments where fungicide was applied compared to the control, obtaining maximum performance in treatments where silicosulfocálcico broth was applied with an average of 1210.07 kg ha-1